Estimation of Human Oral Fraction Dose Absorbed of Simvastatin from Various Formulations using in-situ Single Pass Intestinal Perfusion Method - Verma, Madhu; Nanda, Arun; Chauhan, Iti; Yasir, Mohd.; Majhi, Sagarika; Rajkumari; Sharma, Meenakshi (Drug Delivery Letters, 2023)
Background: SIM is a poorly water-soluble drug with dissolution-dependent bioavailability. A solid dispersion and self-emulsifying drug delivery system was developed, optimized, and evaluated to improve its bioavailability. The permeability coefficient in rats was determined using the in-situ single-pass intestinal perfusion (SPIP) technique. Further, the permeability coefficient (Peff, humans) was used to calculate the permeability and fraction of SIM bioavailable to humans which have not yet been reported for these formulations.Objective: To estimate and compare various formulations of Simvastatin (SIM) for bioavailable fraction to humans (Fa) as a function of solubility enhancement.Methods: In this study, the preparation and evaluation of SIM formulations i.e., Self-emulsifying drug delivery system (SEDDS) and Solid dispersions (SD) are discussed in brief. An uncomplicated, precise, and accurate HPLC method was validated for simultaneous determination of SIM and phenol red as per ICH guidelines. A comparative in-vitro dissolution test, pharmacokinetic studies, and in-situ SPIP technique in rats were carried out amongst optimized formulations of SIM-SD and SIM-SEDDS, SIM suspension (SIM-SUSP), and SIM marketed preparation (SIM-MP).Results: The HPLC method was successfully validated. In-vitro dissolution test displays that both the SIM formulations i.e., SIM-SEDDS and SIM-SD shows better dissolution rate than SIM-MP and SIM-SUSP. Pharmacokinetic studies revealed that SIM-SEDDS, SIM-SD, and SIM-MP showed significant differences when compared to SIM-SUSP in terms of Cmax, [AUC] 0-∞ at ≤ 0.05. The comparison of permeability coefficient between SIM SEDDS vs. SIM MP and SIM SEDDS vs. SIM SD were non-significant. In contrast, SIM- SUSP vs. all other formulations were significantly different at ≤ 0.05 (employing two-way ANOVA followed by post-Bonferroni Test). Fa for SIM SUSP, an optimized formulation of SIM-SEDDS, SIM-MP, and SIM-SD are 0.353, 0.977, 0.975, and 0.987 respectively. It is revealed that SIM-SEDDS and SIM-SD showed enhanced absorption and the results are confirmed by in-vitro data, pharmacokinetic studies, and In-situ SPIP techniques.Conclusion: The permeability prediction method is a rapid and economical method for screening chemical compounds with the least possible utilization of resources. So, its use can be extended in prime and initial screening prototypes for the evaluation of compounds in the early stages of their formulations.
Keywords: two-way ANOVA